Scythianism and Eurasianism: Tracing Russian strategic culture - Malešević Matija (Srpska Politička Misao)
Research of the ideological foundations of Scythianism and Eurasianism underlines the conceptual affinity between these two movements, as well as their cause-and-effect relationship. These phenomena are embedded within the particular historical and social context. They are part of Russian socio-political thought during the pivotal years of the Great War and the October Revolution, and represent a medium through which we can reconstruct the prevailing "spirit of the time." Nevertheless, the focal point of this study is oriented towards the future, not the past. This is due to the fact that the ideas emanating from these movements hold a greater contemporary relevance than they did a century ago. We conclude that both Scythianism and Eurasianism are not just part of history, but rather far-reaching visions being realized before our eyes. From a contemporary perspective, the Scythians are pioneers of a "creative era" whose intuition and elan vital set Russia on a new civilizational trajectory. Their significance becomes particularly pronounced on the threshold of tectonic international changes and apocalyptic forecasts that can no longer be remedied through "political reforms", but solely through systemic changes. Similar to the period before the First World War, an avantgarde strategic culture emerges as a suitable solution, especially taking into account the dispersion of global power in the collective West.